The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1002/1097-0142(19810101)47:1<184::aid-cncr2820470130>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of central nervous system acute leukemia in adults

Abstract: Central nervous system (CNS) involvement occurred in 45 of 222 (20.3%) leukemic adults achieving bone marrow (BM) complete remission (CR), including 12 of 23 (52%) acute undifferentiated leukemia (AUL), 12 of 32 (39%) lymphoma leukemia, 5 of 26 (19%) acute lymphoblastic leukemia, and 16 of 142 (11%) acute myelogenous leukemia. Risk factors for CNS disease were lactic dehydrogenase (LDH) greater than or equal to 25,000/mm3. AUL morphology, age less than 20 years, and extramedullary involvement were most signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(47 citation statements)
references
References 23 publications
2
44
1
Order By: Relevance
“…This disease develops in approximately 5% to 8% of patients with solid tumors, especially adenocarcinomas of the breast and lung as well as melanomas (1,2), in 5% to 29% of patients with non-Hodgkin's lymphoma (1,3), and in 11% to 70% of patients with leukemia (1,4). Tumor involvement of the leptomeninges is also a serious problem in certain primary neural tumors including medulloblastomas (5).…”
Section: Recei×ed 14 October 1999 Accepted 1 April 2000 Original Articlementioning
confidence: 99%
“…This disease develops in approximately 5% to 8% of patients with solid tumors, especially adenocarcinomas of the breast and lung as well as melanomas (1,2), in 5% to 29% of patients with non-Hodgkin's lymphoma (1,3), and in 11% to 70% of patients with leukemia (1,4). Tumor involvement of the leptomeninges is also a serious problem in certain primary neural tumors including medulloblastomas (5).…”
Section: Recei×ed 14 October 1999 Accepted 1 April 2000 Original Articlementioning
confidence: 99%
“…Central nervous system involvement at first relapse was documented in 6 patients: 2 had isolated cases, one had another extramedullary relapse location, and half had simultaneous bone marrow involvement, as reported in other studies. 6,10 The median time to central nervous system relapse was seven months (range 1-16 months) compared with nine months (range 1-167 months) for isolated bone marrow relapse. The median time to central nervous system relapse reported here is sooner than the 12 and 19 months reported by Castagnola et al 10 and Holmes et al, 7 respectively, in adult AML patients, but similar to the four months described in a pediatric series.…”
Section: Resultsmentioning
confidence: 99%
“…3 The present study showed an overall 5-year cumulative incidence of central nervous system relapse of 1.3% (either isolated or combined with bone marrow relapse), which is lower than the previously reported incidence of 3-11%. [4][5][6][7][8][9][10] The different statistical methods used to calculate the incidence in our study (competing risk analysis using the CI) compared with others (crude incidence) may explain, at least in part, our different rate of central nervous system relapse. Another explanation is that most previous studies were performed exclusively in patients treated with old chemotherapy protocols in the 1980s, 4-9 whereas in our series most of the patients were treated with modern protocols.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations